When 'less is more': The rationale for an adaptive toolbox to manage the risk and uncertainty of rework. (December 2022) - Love, Peter E.D.; Matthews, Jane
Abstract: Determining the risk and uncertainty of rework in construction has received limited attention due to a paucity of information about its frequency and causes. Errors made during construction, which may require rework, can go undetected, manifesting as an engineering failure during an asset's operation and thus jeopardise system safety. Therefore, this paper addresses the following research question: How can practitioners make better decisions to mitigate the risk and uncertainty of rework during the construction of infrastructure assets and ensure system safety? Using a mega-transport infrastructure asset as a case setting, we adopt an interpretative line of inquiry and examine people's experiences with managing the risk and uncertainty of rework under the auspices of a sense-making lens. Our analysis revealed that heuristics were being used informally to determine rework risks and uncertainties due to the absence of information, resulting in them becoming curiosities as the same mistakes were repeated and learning stymied. We suggest that developing an adaptive-box tool comprising heuristics can provide the much-need theoretical foundation to effectively manage the risk and uncertainty of rework. Such heuristics would be adaptable to different situations as they are fitted to the environment through evolution and/or learning by amending them successively in small steps. Highlights: There is an absence of research that has examined the risk and uncertainty of rework in construction. Using the lens of sensemaking the risks and uncertainties of rework in a transport mega-project are examined. Heuristics are informally used to determine rework risks and uncertainties due to the absence of information. Suggests an adaptive toolbox' of ecologically rational heuristics is needed to effectively manage the risk and uncertainty of rework.